Menelisik Kontribusi Penyiaran Televisi untuk Visi Indonesia Generasi Emas 2045 - Alamsyah, Feri Ferdinan; Irawan, Enjang Pera; Valdiani, Dini (JURNAL KOMUNIKATIO, 2025)
A preventive idea for Indonesia's Generasi Emas 2 045 challenges in facing the demographic dividend in the future. This demographic dividend is a social threat that has tremendous impact, if not dealt with properly. All stakeholders, including television broadcasting industry, can contribute. Komisi Penyiaran Indonesia (KPI) stated that the television industry has great potential. This research aims to show the potential of the television industry in supporting this idea. The method used is a qualitative approach with descriptive analysis. Through the Desk study tradition, a research method that provides initial ideas on existing or secondary data. Data is obtained from references related to the reality of the study, such as government reports, previous research results, etc. The results of this research show: (1) Television has better advantages than new media in terms of credibility, (2) Television needs to expand into new media for wider distribution of content, (3) In the context of intervention, the government needs to strengthen the partnership system with television broadcasting industry, which is based on the principle of mutual benefit. This article can provide implications as one of the basics in developing television broadcasting culture after digitalization, which is part of mass communication.